Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1038/srep38123
|View full text |Cite|
|
Sign up to set email alerts
|

Crystallizing highly-likely subspaces that contain an unknown quantum state of light

Abstract: In continuous-variable tomography, with finite data and limited computation resources, reconstruction of a quantum state of light is performed on a finite-dimensional subspace. In principle, the data themselves encode all information about the relevant subspace that physically contains the state. We provide a straightforward and numerically feasible procedure to uniquely determine the appropriate reconstruction subspace by extracting this information directly from the data for any given unknown quantum state o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…This procedure requires nothing more than data obtained from a set of commuting measurements. As in [25], the extraction of the physical sector does not depend on any other assumptions or calibration details about the source. By construction, this procedure has a linear complexity in the dimension of the physical sector.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This procedure requires nothing more than data obtained from a set of commuting measurements. As in [25], the extraction of the physical sector does not depend on any other assumptions or calibration details about the source. By construction, this procedure has a linear complexity in the dimension of the physical sector.…”
Section: Introductionmentioning
confidence: 99%
“…In reference [25], we showed that, when the measurement device is calibrated, one can systematically extract the physical sector (that is, both the Hilbert-space support and dimension) and simultaneously reconstruct any unknown state directly from the measurement data without any assumption about the state. In this paper, we introduce an even more efficient procedure that extracts the physical sector of any state from the data without state reconstruction and provide the pseudocode.…”
Section: Introductionmentioning
confidence: 99%